The Early Elementary School Abbreviated Math Anxiety Scale (the EES-AMAS): A New Adapted Version of the AMAS to Measure Math Anxiety in Young Children - Primi, Caterina; Donati, Maria A.; Izzo, Viola A.; Guardabassi, Veronica; O’Connor, Patrick A.; Tomasetto, Carlo; Morsanyi, Kinga (Frontiers in Psychology, 2020)
Over the last decade, there has been increasing interest in understanding how and when math anxiety (MA) develops. The incidence and effects of MA in primary school children, and its relations with math achievement, have been investigated. Nevertheless, only a few studies have focused on the first years of primary school, highlighting that initial signs of MA may emerge as early as 6 years of age. Nevertheless, there are some issues with measuring MA in young children. One of these is that, although several scales have been recently developed for this age group, the psychometric properties of most of these instruments have not been adequately tested. There is also no agreement in the number and identity of the factors underlying MA at this young age. Some scales also consist of several items, which make them impractical to use in multivariate studies, which aim at the simultaneous measurement of several constructs. Finally, most scales have been developed and validated in US populations, and it is unclear if they are appropriate to be used in other countries. In order to address these issues, the current studies aimed at developing a short, new instrument to assess MA in early elementary school students, the Early Elementary School Abbreviated Math Anxiety Scale (the EES-AMAS). This scale is an adapted version of the Abbreviated Math Anxiety Scale (AMAS; Hopko et al., 2003), which is one of the most commonly used scales to measure MA and has been shown to be a valid and reliable measure across a number of countries and age groups. The psychometric properties of the new, 9-item scale have been investigated by taking into account its dimensionality, reliability, and validity. Moreover, the gender invariance of the scale has been verified by showing the measurement equivalence of the scale when administered to male and female pupils. We have also tested the equivalence of the scale across languages (Italian and English). Overall, the findings confirmed the validity and reliability of the new scale in assessing the early signs of math anxiety and in measuring differences across genders and educational contexts.